1997
DOI: 10.3109/10520299709082210
|View full text |Cite
|
Sign up to set email alerts
|

Nonradioactive in Situ Hybridization Histochemistry in Leukemic and Nonleukemic Culture

Abstract: Technical limitations are associated with conducting successful in situ hybridization. In this study, three cell types including a tumor neuroblastoma cell line (Neuro-2a), an oligodendrocyte primary culture, and a nonneuronal acute lymphoblastic leukemia cell line (Reh) were used to conduct successful nonradioactive in situ hybridization. Two cDNA probes were used. A 1 kb probe was used to identify the expression of proteolipid protein (PLP) mRNA in a primary culture of oligodendrocytes. A 760 bp cDNA was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…The nonradioactive in situ hybridization protocol used for tissue sections is essentially similar to the nonradioactive in situ hybridizaton procedure used on our glial cell cultures (Maki et al 1997;Granneman et al 1998). We found that labeling small amounts of probe gave the most intense staining of cells, and our at- The neuroepithelial layer is thickened at the dorsolateral border.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The nonradioactive in situ hybridization protocol used for tissue sections is essentially similar to the nonradioactive in situ hybridizaton procedure used on our glial cell cultures (Maki et al 1997;Granneman et al 1998). We found that labeling small amounts of probe gave the most intense staining of cells, and our at- The neuroepithelial layer is thickened at the dorsolateral border.…”
Section: Discussionsupporting
confidence: 51%
“…No staining was found in the control tissue. Our previous in situ hybridiztion studies (Maki et al 1997;Granneman et al 1998) with pBR322 DIG-labeled cDNA produced no signal using a similar procedure, and RNAse treatment also abolished the signal.…”
Section: In Situ Hybridizationmentioning
confidence: 83%